Population, pensions, and endogenous economic growth - Heer, Burkhard; Irmen, Andreas (Discussion paper series, 2008)
We study the effect of a declining labor force on the incentives to engage in labor-saving technical change and ask how this effect is influenced by institutional characteristics of the pension scheme. When labor is scarcer it becomes more expensive and innovation investments that increase labor productivity are more profitable. We incorporate this channel in a new dynamic general equilibrium model with endogenous economic growth and heterogeneous overlapping generations. We calibrate the model for the US economy. First, we establish that the net effect of a decline in population growth on the growth rate of per-capita magnitudes is positive and quantitatively significant. Second, we find that the pension system matters both for the growth performance and for individual welfare. Third, we show that the assessment of pension reform proposals may be different in an endogenous growth framework as opposed to the standard framework with exogenous growth.
Keywords: 1899-1999; Graue Literatur